Effects of supplemental citrulline malate ingestion during repeated bouts of lower-body exercise in advanced weightlifters - Wax, B.; Kavazis, A. N.; Weldon, K.; Sperlak, J. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this investigation was to test the efficacy of citrulline malate supplementation on exercise performance, blood lactate, heart rate, and blood pressure during lower-body dynamic resistance exercise. We hypothesized that citrulline malate ingestion before performing submaximal repeated bouts of multiple lower-body resistance exercises would improve performance. Twelve advanced resistance-trained male subjects participated in a randomized, counterbalanced, double-blind study. Subjects were randomly assigned to placebo (PL) or citrulline malate (8 g) groups and then performed repeated bouts of multiple lower-body resistance exercise. Specifically, subjects performed 5 sequential sets (60% 1 repetition maximum) to failure on the leg press, hack squat, and leg extension machines. Blood lactate, heart rate, systolic blood pressure, and diastolic blood pressure were determined before and after exercise. The exercise protocol resulted in sequential significant (p = 0.05) decrease in the number of repetitions in all 3 exercises. However, subjects in the citrulline malate group performed significantly (p = 0.05) higher number of repetitions during all 3 exercises compared with PL group. Blood lactate and heart rate were significantly increased (p = 0.05) after exercise compared with before exercise but were not significantly different between citrulline malate and PL (p > 0.05). No significant (p > 0.05) differences were detected for blood pressure measurements. In conclusion, our results suggest that citrulline malate supplementation may be beneficial in improving exercise performance during lower-body multiple-bout resistance exercise in advanced resistance-trained men.